Evaluasi Kurikulum - Sari, Arini Vika; Pariyasto, Sofyan; Simamora, Winri; Syahputra, Ridwan (Jurnal Studi Multidisiplin Qomaruna, 2025)
Curriculum evaluation is a strategic step in ensuring the quality of education. This article examines various aspects of curriculum evaluation through a literature review of academic sources published between 2020 and 2024. The findings indicate that the most frequently criticized aspects of curriculum implementation include the misalignment of instructional content with students' needs and characteristics, as well as the limited relevance of curriculum content to advances in knowledge and labor market demands. In addition, qualitative evaluation models—such as in-depth interviews and participatory observation—are recommended, as they are capable of capturing dimensions of the learning process that are often overlooked by quantitative approaches. This review highlights the importance of selecting appropriate evaluation models as a foundation for continuous improvement and the development of a curriculum that is more adaptive to change.